Prevenzione degli infortuni sul lavoro nelle fonderie: intervento multidisciplinare e verifica di efficacia / Prevention of occupational injuries in foundries: multidisciplinary intervention and evaluation of effectiveness - Porru, S.; Arici, C.; Calza, et al., S. (La Medicina del Lavoro, 2009)
Dati disponibili in letteratura indicano carenza di studi sul campo per la valutazione di efficacia di interventi finalizzati alla prevenzione degli infortuni sul lavoro (IL), particolarmente nelle fonderie. Dal 1999-2000, presso 2 fonderie (ghisa=A, metalli non ferrosi=B), caratterizzate da elevati indici infortunistici e problematiche gestionali, è stato intrapreso un intervento multidisciplinare, coordinato dal Medico del Lavoro e articolato in valutazione del rischio, raccolta ed elaborazione dati, interventi tecnico-organizzativo-procedurali, SS, informazione/formazione, primo soccorso. Nel 1997-2007, si sono verificati rispettivamente 522 (A) e 90 (B) IL, con 10.500 (A) e 2.300 (B) giorni di prognosi. L’analisi statistica ha documentato un significativo decremento degli indici infortunistici dopo l’intervento, con miglioramento di vari indicatori di esito. Intervento analogo basato su principi EBP è in corso in altre 50 fonderie. Prevention of occupational injuries in foundries: multidisciplinary intervention and evaluation of effectiveness Background: there is a lack of field studies aimed at reducing occupational injuries (OI), particularly in foundries. Objectives: to evaluate effectiveness of multidisciplinary intervention in foundries. Methods: the study was carried out in two foundries (cast-iron=A, non-ferrous=B). Since 1999-2000, a multidisciplinary intervention was developed, by a team managed by the occupational physician, including safety personnel and workers’ representatives. Interventions regarded maintenance, protective equipment, procedures, training, health surveillance (HS), fitness for work, first aid. The desired outcome was a reduction in injury rates. Results: In foundries A and B, respectively 522 and 90 OI occurred in 1997-2007, accounting for 10,500 and 2,300 lost workdays. Statistical analysis showed a significant decrease in incidence and frequency in both foundries. HS allowed for human factor and fitness for work evaluation, return-to-work management. Safety culture, behaviour and procedures positively changed. Conclusions: the study was effective in reducing OI rates and improving a number of secondary outcomes. The same intervention, taking into account Evidence Based Prevention, is ongoing in about 50 foundries.